Bangkong: Eksplorasi Ritme dan Timbre Suara Katak secara Akustik pada Rancangan Instrumen Drumkusi - Wijaya, Yonathan; Wayan Dibia, I; Ardini, Ni Wayan (Journal of Music Science, Technology, and Industry, 2021)
Purpose: The creation of this work is directed at producing a drumming style in another way and a drum cussion solo composition. Research method: This creation uses the roger sessions creation method, namely inspiration, conception, and execution. Results and discussion: The creative form of Bangkong's musical work is to transform the frog's voice which is formulated in the formulation of the problem into three parts in this work, where each part of the work is given the freedom to improvise but is conceptualized. Implication: Bangkong is processed in such a way as to produce three forms of Bangkong rhythms to become an original, intact, and characterized musical work that can be used by musicians, especially drummers and percussionists, to achieve a good reputation by having a new playing style.